Cross-breeding local chickens - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2004)
Childwell Nyirenda of the Zambian Ministry of Agriculture explains how cross-breeding can improve productivity in local birds.